2018
DOI: 10.1017/s0033291718001356
|View full text |Cite
|
Sign up to set email alerts
|

Rapid antidepressant effects of the psychedelic ayahuasca in treatment-resistant depression: a randomized placebo-controlled trial

Abstract: To our knowledge, this is the first controlled trial to test a psychedelic substance in treatment-resistant depression. Overall, this study brings new evidence supporting the safety and therapeutic value of ayahuasca, dosed within an appropriate setting, to help treat depression. This study is registered at http://clinicaltrials.gov (NCT02914769).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
564
2
43

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 599 publications
(644 citation statements)
references
References 53 publications
35
564
2
43
Order By: Relevance
“…Moreover, SPECT imaging showed that ayahuasca administration was associated with increased blood perfusion in the left nucleus accumbens, right insula, and left subgenual area, brain regions associated with emotional processing and the therapeutic effects of traditional antidepressants. These results were partially replicated by our group in a recent parallel arm, double-blind, randomized, placebo-controlled trial in which 35 patients with treatment-resistant major depression received a single dose of ayahuasca or placebo 43 . Compared with patients that received placebo, patients that received ayahuasca had lower depressive symptoms seven days after drug administration.…”
Section: Therapeutic Potentialsmentioning
confidence: 74%
See 4 more Smart Citations
“…Moreover, SPECT imaging showed that ayahuasca administration was associated with increased blood perfusion in the left nucleus accumbens, right insula, and left subgenual area, brain regions associated with emotional processing and the therapeutic effects of traditional antidepressants. These results were partially replicated by our group in a recent parallel arm, double-blind, randomized, placebo-controlled trial in which 35 patients with treatment-resistant major depression received a single dose of ayahuasca or placebo 43 . Compared with patients that received placebo, patients that received ayahuasca had lower depressive symptoms seven days after drug administration.…”
Section: Therapeutic Potentialsmentioning
confidence: 74%
“…In our open-label study involving the administration of a single ayahuasca dose to 17 patients with treatment-resistant major depressive disorder, vomiting was the only adverse effect reported and occurred in 47% of the volunteers 42 . In our subsequent randomized controlled trial, the most common adverse reaction were nausea (71%), vomiting (57%), transient anxiety (50%), transient headache (42%), and restlessness (50%) 43 .…”
Section: Safety and Toxicitymentioning
confidence: 93%
See 3 more Smart Citations